Technological planning and social futures - Jantsch, Erich (Associated Business Programmes, 1972)
This book consists mainly of articles which the author has published ever since his survay of methods and organisation of technological forecassting, undertake for the organisation of economic Co-operation and development has led him to this broad subject.